Taxonomy of the leafhopper genus Angolaia (Hemiptera: Cicadellidae: Deltocephalinae: Selenocephalini) with description of a new species from Zambia - Xu, Deliang; Zhang, Yalin (Zootaxa, 2022)
The African leafhopper genus Angolaia Linnavuori & Al-Ne’amy, 1983 (Cicadellidae: Deltocephalinae: Selenocephalini: Selenocephalina) is reviewed, including description of the new species, Angolaia picea sp. nov., from Zambia. An updated checklist with distribution and a key to males in this genus are also provided. Type specimens of this new species are deposited in the Illinois Natural History Survey, University of Illinois, Champaign, Illinois, USA (INHS).